Investigation on the properties of carbon filler reinforced polymers (CFP) 3D printing - Quah, Zong Wei (Nanyang Technological University, 2024)
Polyethylene Terephthalate (PET) is a commonly used thermoplastic polymer used for food containment. The reason for its prevalent use is its low cost and ease to manufacture. With these two reasons most manufacturers of PET products see it as a single use product. However, plastics tend to be non-biodegradable. This means natural degradation either does not occur or takes a long time to happen. This means that without ways to deal with PET waste, there will be a stockpiling of PET waste which poses detrimental effects on the environment. With these negative consequences, many recycling techniques have been used. PET is highly recyclable through physical means like grinding into pellets and reforming into bottles and packaging. However, this physical process has two main drawbacks being the degradation of PET properties and the high cost of recycling coloured PET products. Hence, often coloured PET products still end up in landfills. Hence, this study focuses on exploring the upcycling of PET bottles through the usage of 3d printing. Specifically, Sheet 3d printing which is rarely explored with regards. To combat the degradation of physical properties from melting and welding carbon filler addition is also explored. PET bottles are made into sheets via a heat press after being cut. Carbon is then added between two layers of PET sheets before being put through a roller to form carbon filler reinforced PET (CFRP) layers of PET and CFRP are then stacked together and printed together to form composite that has the required strength and toughness. Results were found that doping of carbon increases the strength of PET but it causes the composite material to be brittle. Further studies of stacking configurations can be and carbon doping quantities can be done